Peran Pendidikan Agama Kristen dalam Menanamkan Sikap Toleransi Beragama bagi Generasi Milenial - Sihite, Jelita (THEOSOPHIA: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract: Indonesia is a pluralistic country rich in religious, ethnic, racial, linguistic and socio-culturaldiversity. As a plural country, the space for conflict and SARA is wide open so that it often raises variousproblems in it, both religion with other religions, ethnicity with other tribes, and other problems. In addition,Indonesia has a dismal record of religious intolerance to the point of loss of life and property. Intolerance isstill a serious threat to the Indonesian people even though they are already in the Millennium Era, namelythe era of scientific and technological progress. Researchers use library research (Library Research). Libraryresearch is research carried out using literature (library), in the form of books, notes, and reports of previousresearch results. Millennials should be able to play an important role as agents of peace for the world, nation and society. The Millennial generation must realize that progress is an Indonesian reality that cannot bedenied by anyone, which in turn gives birth to a diversity of cultures, customs, languages and beliefs.Pluralism in the context of Indonesia is a unique wealth. To be one nation and one country, as the motto ofthe Indonesian people, namely Bhinneka Tunggal Ika - different but one. In line with the teaching ofChristian Religious Education, tolerance must be carried out based on love. Because without love it isimpossible for one to love one another. This is in accordance with Jesus' teaching to love one another. Lovingothers is the heart of Jesus that must be obeyed and practiced by Christians. That love breeds tolerance formutual respect, respect, and peace for others. Therefore, to realize God's mission for the world to bring peaceto all of His creation, PAK must instill an attitude of tolerance to the Millennial generation, and become thePAK curriculum in the learning process, both at school and in the Church. Abstrak: Indonesia adalah negara majemuk yang kaya dengan keberagaman agama, suku, ras,bahasa, dan sosial budaya. Sebagai negara majemuk, maka ruang konflik dan SARA terbuka lebarsehingga seringkali memunculkan berbagai permasalahan di dalamnya, baik agama dengan agamalain, suku dengan suku lain, dan permasalahan-permasalahan lainnya. Selain itu, Indonesiamemiliki catatan buram mengenai sikap teleransi beragama sampai menghilangkan nyawa, danharta benda. Sikap intoleransi masih menjadi ancaman serius bagi masyarakat Indonesia meskipunsudah berada di Era Milenial yaitu Era kemajuan ilmu pengetahuan dan teknologi. GenerasiMilenial berperan penting menjadi agen perdamaian bagi dunia, bangsa dan masyarakat. GenerasiMilenial harus menyadari bahwa, kemajukan merupakan realitas ke-Indonesiaan yang tidak bisa dipungkiri oleh siapapun, yang pada gilirannya melahirkan keberagaman budaya, adat, bahasadan kepercayaan. Kemajemukan dalam konteks ke-Indonesia menjadi kekayaan yang unik.Menjadi satu bangsa dan satu negara, sebagaimana semboyan bangsa Indonesia yaitu BhinnekaTunggal Ika - berbeda-beda tetapi satu. Selaras dengan pengajaran Pendidikan Agama Kristen,sikap toleransi harus dilakukan berdasarkan kasih. Sebab, tanpa kasih tidak mungkin seseorangdapat mengasihi sesama. Hal ini, sesuai dengan pengajaran Yesus untuk saling mengasihi sesama.Mengasihi sesama merupakan hati Yesus yang harus ditaati dan dilakukan oleh orang Kristen.Kasih itu melahirkan sikap toleransi untuk saling menghargai, menghormati, menghadirkan damaibagi sesama. Oleh karena itu, untuk mewujudkan misi Allah bagi dunia menghadirkan damaisejahtera bagi seluruh ciptaan-Nya, maka PAK harus menanamkan sikap toleransi kepada generasiMilenial, dan menjadi kurikulum PAK dalam proses pembelajaran, baik disekolah maupun di dalam Gereja